Effects of a Bacillus amyloliquefaciens-Konjac glucomannan synbiotic as a functional feed additive on immunity and disease resistance of Labeo rohita - Debaprasad Rath; Tanmoy Gon Choudhury; Suraj Kumar; Sanat Chandravanshi; Narayanaprasad Dash; Janmejay Parhi; Nitesh Kumar Yadav; Dibyendu Kamilya (Animal Feed Science and Technology, 2026)

A comprehensive study on Salmonella enterica serovar Richmond in farmed fish Pangasianodon hypophthalmus: insights into zoonotic potential, virulence and antimicrobial resistance - Satya Narayan Parida; Partha Sarathi Tripathy; Neelesh Kumar; Anuj Tyagi; Ajaya Kumar Rout; Gaurav Kumar; Janmejay Parhi; Bijay Kumar Behera; Promod Kumar Pandey (Folia Microbiologica, 2026)

Molecular characterization and expression profiling of cyp17 in the catfish Clarias magur with insights from molecular docking and molecular dynamics simulation - Maradode Jaywant Raghunath; Dibyajyoti Uttameswar Behera; Papuli Adhikary; Sukanta Nath; Sagar Chandra Mandal; Ajaya Kumar Rout; Bijay Kumar Behera; Janmejay Parhi; Partha Sarathi Tripathy (Aquaculture International, 2026)

Valencene as a novel potential downregulator of THRB in NSCLC: network pharmacology, molecular docking, molecular dynamics simulation, ADMET analysis, and in vitro analysis - Janmejay Pant; Lovedeep Singh; Payal Mittal; Nitish Kumar (Molecular Diversity, 2025)

Freeze-drying of Bacillus amyloliquefaciens COFCAU_P1 probiotics: process optimization, and evaluation of its immunoprotective role in Labeo rohita - Tanmoy Gon Choudhury; Sangita Roy; Suraj Kumar; Debaprasad Rath; Supratim Malla; Partha Sarathi Tripathy; Dibyendu Kamilya; Janmejay Parhi; Ratan Kumar Saha; Arun Bhai Patel (Aquaculture International, 2025)

Chandra’s surface thermophysical experiment (ChaSTE) onboard Chandrayaan 3 Lander - Nizy Mathew; K. Durga Prasad; Dinakar Prasad Vajja; V. Aasik; Fazil Mohammad; P.P. Pramod; M. Satheesh Chandran; Kiran John Antony; M. Ram Prabhu; M.B. Dhanya; Manu V. Unnithan; Shiju G. Thomas; et al. (Advances in Space Research, 2025)

Effect of Stocking Density on Growth, Water Quality Changes and Cost Efficiency of Butter Catfish (Ompok bimaculatus) during Seed Rearing in a Biofloc System - Snigdha S. Majhi; Soibam Khogen Singh; Pradyut Biswas; Reshmi Debbarma; Janmejay Parhi; Soibam Ngasotter; Gusheinzed Waikhom; Dharmendra Kumar Meena; Ayam Gangarani Devi; Sudhanshu S. Mahanand; K. A. Martin Xavier; Arun Bhai Patel (Fishes, 2023)
Biofloc technology is a modern-day high-density fish culture system employing heterotrophic conversion of nitrogenous waste into useful flocs for water quality control and improved welfare. However, optimization of the stocking density for the target species during seed rearing is the key to a successful farming operation. The study evaluated the effect of different stocking density on the growth, feed utilization, digestive physiology and economics in a biofloc-based seed rearing of butter catfish, O. bimaculatus. Advanced fry (1.21 ± 0.08 g) was reared in a zero-water exchange biofloc system for 90 days at stocking densities of 0.5 g/L(T1), 1.0 g/L(T2), 1.5 g/L(T3) and 2.0 g/L(T4). The observed water quality indicates a reduction in DO and pH in T4, while the total ammonia nitrogen and nitrite levels remained low in T1. Among the groups, highest weight gain was noticed in the lowest stocking density (0.5 g/L) (p

CRISPR/Cas Genome Editing—Can It Become a Game Changer in Future Fisheries Sector? - Suvra Roy; Vikash Kumar; Bijay Kumar Behera; Janmejay Parhi; Sipra Mohapatra; Tapas Chakraborty; Basanta Kumar Das (Frontiers in Marine Science, 2022)
Fisheries and aquaculture are the fastest-growing food-producing sector and rapidly becoming an important element for the global food security since they are the primary source of seafood and high animal protein in the human diet. Genome editing offers new possibilities such as the clustered regularly interspaced palindromic repeats (CRISPR)/CRISPR-associated protein (Cas9) technology, which has the potential to accelerate the sustainable genetic improvement in fisheries and aquaculture. The CRISPR/Cas9 system has four key components, namely, target DNA, Cas9, the protospacer adjacent motif sequence, and the guide RNA or single-guide RNA. CRISPR/Cas is cheaper, easier, and more precise than the other genome editing technologies and can be used as a new breeding technology in fisheries and aquaculture to solve the far-reaching challenges. The attributes like high fecundity, external fertilization, short generation interval, the established method of breeding, and the larval rearing of most aquaculture species have advantages for CRISPR/Cas9 genome editing applications. CRISPR/Cas9 has recently been applied to the traits valued in some aquaculture species (almost >20 species), targeting the main traits of traditional genetic improvement initiatives like growth, disease resistance, reproduction, sterility, and pigmentation. Genome editing can fast forward the breeding process with precision where changes occur in the targeted genes. The probability of desired changes occurring and passing the trait in the next generation is high, so it takes 1-3 generations to establish a breed. Moreover, CRISPR/Cas genome editing rapidly introduces favorable changes by disrupting genes with targeted minor changes, in contrast to transgenesis, which introduces foreign genes into the host genome and thereby alleviates major public concerns on safety. Although the CRISPR/Cas technology has a tremendous potential, there are several technical challenges and regulatory and public issues concerning the applications in fisheries and the aquaculture breeding sector. Nonetheless, the exciting point in the CRISPR/Cas9 genome editing is that two CRISPR-edited fish, namely, red sea bream and tiger puffer developed by the Kyoto-based startup got approval and are now on the market for sale, and another fish, FLT-01 Nile tilapia developed by the AquaBounty, is not classified under genetically modified organism regulatory. However, there is still a way to go before it revolutionizes and becomes viable in commercial aquaculture as the new breeding technology for aquaculture-important traits and species.

Changes in Bacterial Composition During Maturing Stages of Salt Fermentation of Pangas ( Pangasianodon hypophthalmus ) - Bahni Dhar; Binaya B. Nayak; Ranendra K. Majumdar; Amjad K. Balange; H. Sanath Kumar; Partha Sarathi Tripathy; Janmejay Parhi (Journal of Aquatic Food Product Technology, 2022)

Differential Expression of Thymoquinone and Its Localization in Different Parts of Nigella sativa L. - Garima Gupta; Mohammed Shariq Iqbal; Brijesh Pandey; Janmejay Kumar Srivastava (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Effect of miconazole nitrate on immunological response and its preventive efficacy in Labeo rohita fingerlings against oomycetes Saprolegnia parasitica - Mukta Singh; Ratan Kumar Saha; Himadri Saha; Janmejay Parhi (Journal of Fish Diseases, 2018)
This study evaluated the effect of sublethal doses of antifungal drug miconazole nitrate ( MCZ ) on immunological responses and its role as a prophylactic drug against S. parasitica in Labeo rohita fingerlings. Fish were fed with sublethal doses of MCZ , that is, T1—6.30 mgMCZ kgBW −1 , T2—12.61 mg MCZ kg BW −1 and T3—25.22 mg MCZ kg BW −1 , and sampling was done at different time intervals for 240 hr. Immunological parameters viz. lysozyme activity, oxygen radical production and plasma antiprotease activity showed significant enhancement ( p 0.05) in fish fed with T2 and T3 doses. Expression of immune‐relevant genes such as TLR ‐22 and β2‐M showed significantly higher expression at 6 hr and 24 hr of sampling in both liver and head kidney. However, these genes showed a downregulation after 120 hr of sampling in both the tissues. Preventive efficacy study showed that single dose of MCZ provides protection against oomycetes up to the fourth day of infection. Significantly higher mortality was observed in control diet‐fed fish as compared to fish fed with MCZ medicated diet. Thus, it can be concluded that the MCZ can act as a potent antifungal agent for preventing oomycetes infection as well as to enhance the immune response.